Oxidation state of manganese in LiMn2O4 powders and its effect on electrochemcal properties - Kim, Seon Hye; Lee, Kook Jae; Shim, Kwang Bo; Kim, Chang Sam (PROGRESS IN POWDER METALLURGY, PTS 1 AND 2, 2007)
Lithium manganese oxide (LiMn2O4) powders for lithium ion batteries were synthesized from two separate raw material pairs, LiOH/MnO and LiOH/MnO2. The prepared powders and their electrochemical properties were investigated. Powders calcined at 780 degrees C were composed of a single-phase spinet structure but those treated at 850 degrees C showed a higher intensity ratio of I-400 to I-311, a slightly larger lattice parameter, and an increased discharge capacity by 10% under 3.0 similar to 4.3V voltage range. The XPS study on the oxidation states of manganese repealed that powders made from LiOH/MnO had less Mn3+ ion and gave better battery performances than those from LiOH/MnO2.